Review Artikel: Analisis Kandungan Rhodamin B Dalam Makanan Dan Minuman - Sulastri Sulastri; Riani Riani; Siti Farikha (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Rhodamine B is a synthetic dye that is usually used in the textile and paper industries. According to Permenkes No.239/Menkes/Per/V/85 regarding certain dyes, it states that rhodamine B is a dangerous substance. Rhodamine B is prohibited for use as a food additive because rhodamine B has chelating compounds and chlorine compounds which can cause cancer in humans. Based on the above problems, a review of articles was carried out by collecting journal literature through Google Scholar to analyze the content of rhodamine B compounds in food samples using thin layer chromatography, UV-VIS spectrophotometry, and paper chromatography methods.